LNET – hệ phần mềm xây dựng các mạng WAN và ứng dụng - Lợi, Phí Mạnh (Journal of Computer Science and Cybernetics, 2016)
This article presents the software package LNET in building wide area network. Intranet and industrial applications as well as specific applications are the goals of LNET design.